2013
DOI: 10.1007/s00345-012-1017-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intermittent catheterization on the quality of life of multiple sclerosis patients

Abstract: Intermittent catheterization (IC) in association with overall urinary management, among patients affected by MS, is well accepted and reduces the impact of urinary dysfunction on their quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 27 publications
0
22
0
4
Order By: Relevance
“…The risk of bias and confounding was intermediate in the majority of included studies (Supplementary S2). A favorable risk of bias and confounding profile was found in one study …”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…The risk of bias and confounding was intermediate in the majority of included studies (Supplementary S2). A favorable risk of bias and confounding profile was found in one study …”
Section: Resultsmentioning
confidence: 91%
“…A conflict of interests was disclosed in one study . None of the studies reported on the role of the funding source in the study.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations